Effect of the delta subunit on assembly and proton permeability of the F0 proton channel of Escherichia coli F1F0 ATPase. - Angov, E (1991)
During the assembly of the Escherichia coli proton-translocating ATPase, the subunits of F1 interact with F0 to increase the proton permeability of the transmembrane proton channel. We tested the involvement of the delta subunit in this process by partially and completely deleting uncH (delta subunit) from a plasmid carrying the genes for the F0 subunits and delta and testing the effects of those F0 plasmids on the growth of unc+ and unc mutant E. coli strains. We found that the delta subunit was required for inhibition of growth of unc+ cells. We also tested membranes isolated from unc-deleted cells containing F0 plasmids for F1-binding ability. In unc-deleted cells, these plasmids produced F0 in amounts comparable to those found in normal unc+ E. coli cells, while having only small effects on cell growth. These studies demonstrate that the delta subunit plays an important role in opening the F0 proton channel but that it does not serve as a temporary plug of F0 during assembly, as had been previously speculated (S. Pati and W. S. A. Brusilow, J. Biol. Chem. 264:2640-2644, 1989).